Phase Transitions and Magnetocaloric Properties in MnCo1−xZrxGe Compounds - Anil Aryal; Abdiel Quetz; Sudip Pandey; Igor Dubenko; Shane Stadler; Naushad Ali (Advances in Condensed Matter Physics)
The structural, magnetic, and magnetocaloric properties of MnCo1-xZrxGe (0.01≤x≤0.04) have been studied through X-ray diffraction, differential scanning calorimetry, and magnetization measurements. Results indicate that the partial substitution of Zr for Co in MnCo1-xZrxGe decreases the martensitic transition temperature (TM). For x = 0.02, TM was found to coincide with the ferromagnetic transition temperature (TC) resulting in a first-order magnetostructural transition (MST). A further increase in zirconium concentration (x = 0.04) showed a single transition at TC. The MST from the paramagnetic to ferromagnetic state results in magnetic entropy changes (-ΔSM) of 7.2 J/kgK for ΔH = 5 T at 274 K for x = 0.02. The corresponding value of the relative cooling power (RCP) was found to be 266 J/kg for ΔH = 5 T. The observed large value of MCE and RCP makes this system a promising material for magnetic cooling applications.